Edukasi Dampak Infeksi Saluran Napas Atas (ISPA) dan Pembagian APD Pada Pengerajin Gerabah di Desa Wisata Banyumulek - Hidayati, Diani; Andriana, Ana; Farmananda, Irsandi Rizki (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Tourism in Indonesia, especially through village tourism, aims to preserve traditions, culture, and traditional activities while offering an authentic atmosphere. West Nusa Tenggara (NTB) has numerous village tourism sites; Banyumulek Village in West Lombok is renowned for its pottery art, which is a significant part of local culture. However, pottery artisans face health issues such as respiratory infections (ISPA), coughs, colds, and eye irritation due to air pollution from pottery firing processes. Observations, data collection, and visits to pottery artisans in Banyumulek village identified the main issue as ISPA due to exposure to pottery firing smoke and inadequate use of masks during work. The cause of this issue was identified through group discussions using the Delphi method. To address this problem, education on ISPA and proper mask usage among artisans is proposed. Interventions include educating artisans on the importance of wearing masks while working and distributing free cloth masks to increase awareness and knowledge of ISPA prevention.